Election Management at The General Election Commission of Ambon City - Layn, Safrudin Bustam (Journal of Governance, 2025)
The implementation of elections is very important for a country, because elections are a means of constitutionally changing leaders, gaining legitimacy, and allowing the people to participate in the political process. Implementing the 2014 election was considered successful, but the level of the process in the field still needs to be improved. Some of these problems are directly related to the governance or implementation of the election management function, which greatly affects the function of the Ambon City General Election Commission as a technical institution organizing elections. The study's results indicate that: 1. Implementing management functions at the General Election Commissions of Ambon City in the governance of the 2014 Election still needs to be functional. The organization of the 2014 General Elections showed various challenges faced by the Ambon City General Election Commission, including the lack of harmonious inter-agency relations, low human resource capacity, and limited information technology infrastructure. These conditions become empirical/concrete evidence that can be used as a basis for formulating efforts to simplify the electoral management system; 2. Factors inhibiting the implementation of the functions of the Ambon City General Election Commission are the external institutional relations factor, causing symptoms of disharmony between the General Election Commission and other LPPs (General Election Supervisory Body); the knowledge factor of the apparatus is still very limited due to the limited number of training activities, especially during non-election stages; and inadequate information technology infrastructure. This has the potential to greatly inhibit the implementation of the functions of the Ambon City General Election Commission.